1997
DOI: 10.3109/09273979709055053
|View full text |Cite
|
Sign up to set email alerts
|

The results of surgical treatment in Duane's retraction syndrome

Abstract: In an attempt to evaluate the response to surgical treatment, the surgical outcome of 16 patients with Duane's retraction syndrome (DRS) was investigated. Single horizontal rectus muscle recession, transposition of vertical recti and recession of both horizontal recti were carried out. In one of the four patients with significant globe retraction, Y splitting of the lateral rectus muscle was added to the procedure to overcome the cosmetically unacceptable upshoot. Single horizontal muscle recession surgery was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Our results demonstrated that recession of both horizontal recti may decrease the globe retraction in 75% of the cases and up/downshoots as well as the deviation in primary position and abnormal head posture [Figure 3]. [41] In our series, we concluded that transposition surgery should be kept for those with minimal globe retraction. [41]…”
Section: Treatmentmentioning
confidence: 76%
See 4 more Smart Citations
“…Our results demonstrated that recession of both horizontal recti may decrease the globe retraction in 75% of the cases and up/downshoots as well as the deviation in primary position and abnormal head posture [Figure 3]. [41] In our series, we concluded that transposition surgery should be kept for those with minimal globe retraction. [41]…”
Section: Treatmentmentioning
confidence: 76%
“…[3738394041] In our clinical practice, this is the most commonly used procedure in DS [Figure 2a and b]. Our results demonstrated that recession of both horizontal recti may decrease the globe retraction in 75% of the cases and up/downshoots as well as the deviation in primary position and abnormal head posture [Figure 3].…”
Section: Treatmentmentioning
confidence: 82%
See 3 more Smart Citations